IMPLEMENTASI KEBIJAKAN CIPTA KERJA : STUDI KASUS PELANGGARAN PERJANJIAN KERJA WAKTU TERTENTU (PKWT) - Tursadi, Naa’ilah Desiyana; Camelia, Eksa; Utami, Yeski Putri (Jurnal Hukum Positum, 2024)
This research discusses the implementation of the Job Creation policy in the context of PKWT by highlighting cases of violations that occur. The analysis showed that there were violations of annual leave rights and salary deductions without a valid legal basis, highlighting the importance of strong and objective evidence in performance evaluations to ensure fairness in contract renewals. The conclusion of this study shows that although the UUCK brings significant changes in PKWT regulations, legal uncertainty still often arises when companies do not fulfill workers’ rights or cut salaries during leave. It is important for companies to understand and comply with these provisions and for the government to ensure effective law enforcement to protect the annual leave rights of PKWT workers. This study recommends that the next research focus on ’’Transparent Performance Evaluation in PKWT Contract Renewal’’, Delve into the importance of objective and transparent performance evaluations to ensure fairness in contract renewals, by discussing effective performance appraisal methods and best practices from companies that have implemented a fair performance evaluation system.